The Authority of The Judge to Restore Onerous Obligation: A comparative Study - Tahseen Zaher Younis (QALAAI ZANIST JOURNAL, 2024)
The subject that deals with the study aims at the authority of the judge to restore the burdensome obligation in the event of a contractual defect when achieving emergency conditions, as well as standing on the scope of the judge’s authority when applying the theory of emergency. Conditions of contracts and how to deal with fatigue and difficulties in implementing the contract and balancing the interests of the contracting parties to restore commitment to fatigue and remedy the contractual imbalance